Results of an Online Survey on Intensive Care Management of Patients with Aneurysmal Subarachnoid Hemorrhage in German-Speaking Countries - Myftiu, Anisa; Mäder, Lisa; Aroyo, Ilia; Kollmar, Rainer (Journal of Clinical Medicine, 2024)
Background: The clinical course of patients with aneurysmal SAH (aSAH) is often dynamic and highly unpredictable. Since its management varies between hospitals despite guidelines, this survey aimed to assess the current state of intensive care treatment for aSAH in the German-speaking region and provide insights that could aid standardization of care for aSAH patients in the intensive care setting. Methods: From February 2023 to April 2023, medical professionals of the German Interdisciplinary Association for Intensive Care and Emergency Medicine (DIVI), the Initiative of German Neuro-Intensive Trial Engagement (IGNITE) network and manually recorded clinics with intensive care units were invited to participate in a standardized anonymous online questionnaire including 44 questions. The questionnaire was validated in multiple steps by experts of different specialties including those from the DIVI. A descriptive data analysis was carried out. Results: A total of 135 out of 220 participants answered the survey completely. The results showed that most patients were treated in anesthesia-led intensive care units at university and maximum care hospitals. Aneurysms were usually treated within 24 h after bleeding. If vasospasm was detected, induced hypertension was usually implemented as the first treatment option. In refractory vasospasm, interventional spasmolysis with calcium antagonists was usually carried out (81%), despite unclear evidence. There were significant discrepancies in blood pressure target values, particularly after aneurysm repair or after delayed cerebral ischemia (DCI), as well as in hemoglobin limit values for erythrocyte substitution. Despite the limited level of evidence, most institutions used temperature management (68%), including hypothermia (56%), for severe cases. Conclusions: While we anticipated variations between individual intensive care facilities, our survey identified numerous similarities in the treatment of aSAH patients. Methods such as interventional spasmolysis and temperature management were used frequently despite limited evidence. Our results can serve as a fundamental framework for formulating recommendations for intensive care treatment and planning of multicenter studies.
CRIS-Team Scopus Importer:2025-02-04
Keywords: intensive care medicine; multimodal monitoring; subarachnoid hemorrhage; vasospasm